(untitled) (Journal of Shaheed Suhrawardy Medical College, 2025)
Background: Molar pregnancies are rare and pose unique challenges when a live fetus coexists. This case report sheds light on the intricacies of managing such cases and highlights the scarcity of literature on this subject. The introduction provides an overview of molar pregnancies, emphasizing the rarity of cases involving a live fetus and the challenges in their management. Case: The patient, a 23-year-old gravid woman, exhibited symptoms at 28 weeks, including per vaginal spotting. Following thorough investigations and careful consideration of risks, she opted to continue the pregnancy. The case culminated in a preterm delivery at 34 weeks, resulting in a healthy male baby, weighing 1.8 kg, with no congenital abnormalities. Conclusion: Pregnancy with a hydatidiform mole and a live fetus has a high chance of poor fetal outcome. However, this case indicates that a hydatidiform mole may coexist with a live pregnancy and result in the live birth of a normal fetus. J Shaheed Suhrawardy Med Coll 2023; 15(2): 40-43